Formation of the Intermediate Complex in the Oxidation of Thiourea by Hexacyanoferrate(III) in Acidic Media - Nayak, B.; Bhattamisra, S.D. (Asian Journal of Chemistry, 2010)
A spectrophotometric study of the redox reaction of hexacyanoferrate(III) and thiourea under acidic conditions reveals the existence of an intermediate complex resulting from the outer-sphere complex formation between the oxidant and the substrate. The visible absorption spectrum of the complex has maximum at 560 nm, the absorption coefficient and the equilibrium constant values being 38.25 L mol–1 cm–1 and 16.5 respectively. The thionethiol equilibrium of thiourea as well as the unprotonated form of hexacyanoferrate(III) ion play significant role in the formation of the intermediate complex. Variation of hydrogen ion concentration has enabled the derivation of the rate constant values at 30ºC and I = 1.0 M to vary between 4.254 to 12.562 x 10–4 sec–1.